Intra-Hospital, Inter-Hospital and Intercontinental Spread of ST78 MRSA From Two Neonatal Intensive Care Unit Outbreaks Established Using Whole-Genome Sequencing - Earls, Megan R.; Coleman, David C.; Brennan, Gráinne I.; Fleming, Tanya; Monecke, Stefan; Slickers, Peter; Ehricht, Ralf; Shore, Anna C. (Frontiers in Microbiology, 2018)
From 2009 to 2011 (transmission period [TP] 1) and 2014 to 2017 (TP2), two outbreaks involving community-associated clonal complex (CC) 88-MRSA spa types t186 and t786, respectively, occurred in the Neonatal Intensive Care Unit (NICU) of an Irish hospital (H1). This study investigated the relatedness of these isolates, their relationship to other CC88 MRSA from Ireland and their likely geographic origin, using whole-genome sequencing (WGS). All 28 CC88-MRSA isolates identified at the Irish National MRSA Reference Laboratory between 2009 and 2017 were investigated including 20 H1 patient isolates, two H1 isolates recovered from a single healthcare worker (HCW) two years apart, three patient isolates from a second hospital (H2) and one patient isolate from each of three different hospitals (H3, H4 and H5). All isolates underwent DNA microarray profiling. Thirteen international isolates with similar microarray profiles to at least one Irish isolate were selected from an extensive global database. All isolates underwent Illumina MiSeq WGS. The majority of Irish isolates (25/28; all H1 isolates, two H2 isolates and the H3 isolate) were identified as ST78-MRSA-IVa and formed a large cluster, exhibiting 1-71 pairwise allelic differences, in a whole-genome MLST-based minimum spanning tree (MST) involving all Irish isolates. A H1/H2, H1/H3 and H1 HCW/patient isolate pair each exhibited one allelic difference. The TP2 isolates were characterised by a different spa type and the loss of hsdS. The three remaining Irish isolates (from H2, H4 and H5) were identified as ST88-MRSA-IVa and dispersed at the opposite end of the MST, exhibiting 81-211 pairwise allelic differences. Core-genome MLST and sequence-based plasmid analysis revealed the recent shared ancestry of Irish and Australian ST78-MRSA-IVa, and of Irish and French/Egyptian ST88-MRSA-IVa. This study revealed the homogeneity of isolates recovered during two NICU outbreaks (despite spa type and hsdS carriage variances), HCW involvement in the outbreak transmission chain and the strain’s spread to two other Irish hospitals. The outbreak strain, CC88/ST78-MRSA-IVa, was likely imported from Australia, where it is prevalent. CC88/ST88-MRSA-IVa was also identified in Irish hospitals and was likely imported from Africa, where it is predominant, and/or a country with a large population of African descent.